Analisis Pesan Moral pada Video Klip Pastikan Riuh Akhiri Malammu oleh Grup Band Perunggu - Efiana Salfini; Alex Sobur (UNISBA Press, 2023)
Abstract. The research entitled Moral Messages in Rock Music Video Clips Semiotic Analysis of Roland Barthes in Video Clips Ensure Noisy End Your Night By Bronze Band Group is motivated by how signs are presented as moral messages through video clips that are currently in demand by a wide audience. Video clips are one of the media for musicians to convey meaningful messages to their listeners. This study aims to find out how the moral message in the video clip